El acceso a la educación superior un derecho para las personas con capacidades diferentes - Torres Genovez, Anabell Sofía (2024)
This research work was born with the interest to determine whether or not there are certain barriers that tend to the violation of access to higher education institutions for people with disabilities, therefore, it was investigated as the main problem in this analysis, to determine the inclusiveness of people with disabilities. We proceeded to determine whether the current regulations guarantee the full exercise of the rights of people with disabilities; to know if the application of affirmative actions promotes real and effective equality; to propose mechanisms that provide better opportunities for access to an institution of higher education. To achieve these objectives, it was necessary to use empirical, descriptive, comparative methods; with the application of a mixed approach; exploratory, descriptive research with cross-sectional design as well as surveys and interviews. With the use of the methodology described in the previous paragraph in the contribution of this study for the benefit of people with different abilities from the perspective of the current legal regulations higher education is inclusive, but in the face of certain inaccuracies in the access the results obtained and the analysis to the answers obtained in the surveys and interviews aligned to the stated objectives were incorporated and recommendations are proposed and formulated in such a way that the barriers that have prevented the effectiveness of the application of rights through real and effective equality with appropriate mechanisms for a true inclusive higher education are broken.